Scoping Review: Inhibiting and Supporting Factors of Exclusive Breastfeeding in Teenage Moms: english - Pipiet Mahendra; Sitti Nur Djannah; Lina Handayani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Breast milk has a very important role and is the best nutrition in preventing the onset of disease, and it can save lives and provide healthy growth and development during the first 1000 days of life. Findings in several studies show that adolescent mothers have a shorter duration of breastfeeding and have a lower proportion of breastfeeding initiation when compared to adult mothers, so this scoping review aims to review the inhibiting and supporting factors in adolescent mothers in breastfeeding. This scoping review method uses the Arksey &; O'Malley framework, which was developed using the PEOs framework; in searching and selecting articles through relevant databases, namely Pubmed, Ebsco, and Wiley, and using Grey Literature through Google Scholar; The literature search process used PRISMA Flowchart, and found that from 73 articles there were 7 articles selected based on inclusion and exclusion criteria. The findings based on inhibiting factors show that adolescent mothers lack knowledge about exclusive breastfeeding, practical knowledge in breastfeeding, difficult childbirth or other maternal complications, while supporting factors include maternal education, husband desires and support and support. It can be concluded that previous studies show that breastfeeding among adolescent mothers still requires special attention, which is related to inhibiting factors and very diverse supporting factors that occur among adolescent mothers